2009
DOI: 10.1051/0004-6361/200912645
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic cloud models with bent and oblate cross-section boundaries

Abstract: Context. Magnetic clouds (MCs) are formed by magnetic flux ropes that are ejected from the Sun as coronal mass ejections. These structures generally have low plasma beta and travel through the interplanetary medium interacting with the surrounding solar wind. Thus, the dynamical evolution of the internal magnetic structure of a MC is a consequence of both the conditions of its environment and of its own dynamical laws, which are mainly dominated by magnetic forces. Aims. With in-situ observations the magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 53 publications
3
58
0
Order By: Relevance
“…et al (2007) have shown that the ratio r Bx = B x / B is a function of the true impact parameter y/b for a variety of circular models ( means averaging along the spacecraft trajectory within the MC). Démoulin & Dasso (2009) have extended this . For a fixed y/b value, the derivation of this relation implies dp/db = (dr Bx /db)/(dr Bx,L /dp).…”
Section: Detecting Flux Ropes With Elongated Cross Sectionmentioning
confidence: 69%
“…et al (2007) have shown that the ratio r Bx = B x / B is a function of the true impact parameter y/b for a variety of circular models ( means averaging along the spacecraft trajectory within the MC). Démoulin & Dasso (2009) have extended this . For a fixed y/b value, the derivation of this relation implies dp/db = (dr Bx /db)/(dr Bx,L /dp).…”
Section: Detecting Flux Ropes With Elongated Cross Sectionmentioning
confidence: 69%
“…Another estimation of the impact parameter can be done using the approximation introduced in the simplest form of Eq. (31), B x,cloud / B ≈ 1.2p/R (Démoulin & Dasso 2009b), assuming a cross section roughly circular. We obtain p/R ≈ 0.27 from this method.…”
Section: Impact Parameter From Ace and Ulyssesmentioning
confidence: 99%
“…Column 4 (UlyP1) shows the prediction on Ulysses using l = (ζ ACE + ζ Uly )/2 = 0.7 and m = l (i.e., an isotropic expansion in the plane perpendicular to the cloud axis). Column 5 (UlyP2) shows the prediction on Ulysses using l = 0.7 and m = 1, which corresponds to an expansion such that the cross-section of the magnetic cloud is deformed toward an oblate shape in the plane perpendicular to the cloud axis, with the major axis perpendicular to the global flow speed (e.g., Démoulin & Dasso 2009b). Column 6 (UlyP3) shows the prediction on Ulysses using l = 0.74 and m = 1, which corresponds to an expansion in the direction of the plasma main flow as observed on ACE, emulating the case in which the expansion in this direction was similar to the one observed on ACE almost all the time.…”
Section: Prediction Of the Mean Plasma Density And Magnetic Field On mentioning
confidence: 99%
“…Farrugia et al (1993) and Farrugia, Osherovich, and Burlaga (1995) introduced a cylindrical model incorporating self-similarly expansion in two initially force-free constant-α codes, a cylindrical and a spherical models, and noted that the cylindrical configuration did not maintain the force-free state after it starts to expand. Thereafter, Shimazu and Vandas (2002) provided a modification of the mathematical formalism in order to keep the self-similarly expanding cylindrical model as force-free.…”
Section: Introductionmentioning
confidence: 99%
“…(f) Marubashi and Lepping (2007) include curvature into the classic model. rope (Owens, Merkin, and Riley, 2006;Vandas and Romashets, 2003;Vandas et al, 2006;Démoulin and Dasso, 2009); non-cylindrical flux rope fitting (Mulligan and Russell, 2001;Owens et al, 2012); torus fitting Marubashi and Lepping, 2007). The Grad-Shafranov reconstruction technique (Hu and Sonnerup, 2002;) assumes a structure in magneto-hydrostatic (MHS) equilibrium with an invariant direction, and uses the Grad-Shafranov equation to describe the magnetic field in the structure.…”
Section: Introductionmentioning
confidence: 99%